Sliding tribological performance of B4C-hBN composite ceramics against AISI 321 steel under distilled water condition. Issue 17 (1st December 2017) - Li, Xiuqing; Gao, Yimin; Yang, Qingxia
Abstract: In this paper, the sliding tribological performance of B4 C-hBN composite ceramics with different contents of hBN against AISI 321 steel (a hard-cutting material) under distilled water condition have been evaluated using a pin-on-disc testing machine. The experiment results show that, with the increase of friction distance, the sliding friction coefficient of B4 C/AISI 321 steel pair slightly decreases; however, the sliding friction coefficient of B4 C-30 wt%hBN/AISI 321 steel pair comes down rapidly. With increasing hBN content, the coefficients of wear of both B4 C-hBN pin and AISI 321 steel disc samples have a reducing trend, especially the steady-state coefficient of friction falls significantly to 0.008 from 0.385 as the hBN content is raised to 30 wt% from zero. The possible causes for these results are discussed thoroughly.